Clinical severity of rhinovirus/enterovirus compared to other respiratory viruses in children. Issue 4 (7th May 2014) - Asner, Sandra A.; Petrich, Astrid; Hamid, Jemila S.; Mertz, Dominik; Richardson, Susan E.; Smieja, Marek
<x xml:space="preserve">Abstract</x> Background Human rhinovirus/enterovirus (HRV/ENT) infections are commonly identified in children with acute respiratory infections (ARIs), but data on their clinical severity remain limited. Objectives We compared the clinical severity of HRV/ENT to respiratory syncytial virus (RSV), influenza A/B (FLU), and other common respiratory viruses in children. Patients/Methods Retrospective study of children with ARIs and confirmed single positive viral infections on mid‐turbinate swabs by molecular assays. Outcome measures included hospital admission and, for inpatients, a composite endpoint consisting of intensive care admission, hospitalization >5 days, oxygen requirements or death. Results A total of 116 HRV/ENT, 102 RSV, 99 FLU, and 64 other common respiratory viruses were identified. Children with single HRV/ENT infections presented with significantly higher rates of underlying immunosuppressive conditions compared to those with RSV (37·9% versus 13·6%; P < 0·001), FLU (37·9% versus 22%; P = 0·018) or any other single viral infection (37·9% versus 22·5%; P = 0·024). In multivariable analysis adjusted for underlying conditions and age, children with HRV/ENT infections had increased odds of hospitalization compared to children with RSV infections (OR 2·6; 95% CI 1·4, 4·8; P < 0·003) or FLU infections (OR 3·0; 95% CI 1·6, 5·8; <0·001) and increased odds of severe clinical disease among inpatients (OR 3·0; 95% CI 1·6, 5·6; P = 0·001) when compared to those with FLU infections. Conclusions Children with HRV/ENT had a more severe clinical course than those with RSV and FLUA/B infections and often had significant comorbidities. These findings emphasize the importance of considering HRV/ENT infection in children presenting with severe acute respiratory tract infections.